Prevalence of Helicobacter pylori cagA and vacA genes in Cypriot patients - Krashias, George; Bashiardes, Stavros; Potamitou, Alexia; Potamitis, George S; Christodoulou, Christina (The Journal of Infection in Developing Countries, 2013)
Introduction: The prevalence of H. pylori varies with geographic locations. To date there are no epidemiological data on its prevalence in Cyprus; therefore, we determined the prevalence and molecular characteristics of H. pylori infection in Cypriot patients. Methodology: DNA extracted from 103 gastric biopsies was analyzed for the presence of H. pylori by PCR using primers for ureA. H. pylori-positive biopsies were characterized by PCR using specific primers for cagA and vacA genes. The presence of clarithromycin-associated resistant mutations such as A2143G, A2142G, A2142C in 23S rRNA gene of H. pylori-positive patients was determined using a real-time PCR allelic discrimination assay. Results: H. pylori was detected in 41 (39.8%) biopsies and, out of these, 17 (41.5%) tested positive for the cagA gene. The vacA alleles m1, m2, s1a, s1b, and s2 were detected in 7 (17.1%), 34 (82.9%), 12 (29.3%), 2 (4.9%), and 22 (53.7%) isolates, respectively. One (2.4%) biopsy was vacA s1a and s2-positive while one (2.4%) was positive for vacA s1a, s1b, and s2. Three (7.3%) biopsies were untypable for vacA s1, s1b, and s2. The majority (35; 85.4%) of strains were susceptible to clarithromycin while two (4.9%) had the A2143G mutation. Three (7.3%) had a mixture of an A2143G point mutant and susceptible strains while one (2.4%) had a mixture of an A2142G point mutant and susceptible strains. Conclusions: The distribution of the virulence factors cagA and vacA in the Cypriot strains resembled that of strains circulating in Middle Eastern countries geographically close to Cyprus.